Reducing the mortality rate of hepatitis and liver cancer in Japan. (2nd May 2017) - Iwane, Shinji; Oeda, Satoshi; Eguchi, Yuichiro
Abstract: The Basic Act on Hepatitis Countermeasures issued in 2009 states the comprehensive measures that can be taken against viral hepatitis as well as the responsibility that the national government, local governments, health insurance provides, physicians, and citizens should take in these measures, thereby organically facilitating the construction of a hepatitis management system in Japan. In addition, the Committee for the Clinical Management of Hepatitis has established branches in each prefecture to create a hepatitis management network for public hepatitis screening facilities, primary care physicians, medical institutions specializing in hepatitis, and primary hospitals for cooperative medical care of liver diseases to address regional hepatitis‐related issues.